2017
DOI: 10.1111/mec.13971
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of genetic differentiation in a generalist insect‐pollinated herb across spatial scales

Abstract: The isolation-by-distance model (IBD) predicts that genetic differentiation among populations increases with geographic distance. Yet, empirical studies show that a variety of ecological, topographic and historical factors may override the effect of geographic distance on genetic variation. This may particularly apply to species with narrow but highly heterogeneous distribution ranges, such as those occurring along elevational gradients. Using nine SSR markers, we study the genetic differentiation of the monta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Muñoz‐Pajares et al. () also found that both spatial/environmental variables and historical factors play important roles in shaping patterns of genetic differentiation in a montane herb at different spatial scales. The SDMs suggested that P. tibetica and P. fasciculata have adapted to their specific ecological niches (i.e., different predicted distributions; Figure ), and such different ecological niches have influenced their population divergence as indicated by GLMM.…”
Section: Discussionmentioning
confidence: 97%
“…Muñoz‐Pajares et al. () also found that both spatial/environmental variables and historical factors play important roles in shaping patterns of genetic differentiation in a montane herb at different spatial scales. The SDMs suggested that P. tibetica and P. fasciculata have adapted to their specific ecological niches (i.e., different predicted distributions; Figure ), and such different ecological niches have influenced their population divergence as indicated by GLMM.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, historical factors (i.e., past climatic fluctuations) were inferred to drive large-scale spatial genetic structure in this species (see below). Similar spatial, environmental, and historical factors have been suggested to drive spatial genetic patterns in its closely related species P. tibetica ( Ren et al., 2018 ) and in a montane pollination-generalist herb ( Muñoz-Pajares et al., 2017 ). By contrast, for P. nutans , another closely related species of P. fasciculata , geographic isolation played an important role in driving population divergence ( Ren et al., 2018 ), while for the plant species Restio capensis that occurs in the Cape Floristic Region of South Africa, another biodiversity hotspot in the world, climatic variables were the major drivers of population divergence ( Lexer et al., 2014 ).…”
Section: Discussionmentioning
confidence: 82%
“…Yet, recent empirical studies have put forward that geographic distance by itself fails to fully explain the genetic variation observed in natural systems (e.g., Shafer and Wolf, 2013). In fact, geographic, environmental, historical, and intrinsic factors (e.g., mating system) have been suggested to simultaneously act as drivers of spatial genetic patterns at different spatial scales (Wang et al, 2013;Muñoz-Pajares et al, 2017;Ren et al, 2017). Identifying the factors that drive the genetic structure of a plant species is an important first step not only to understand speciation, adaptation, and genetic change (Antonovics, 1968), but also to help in population management.…”
Section: Introductionmentioning
confidence: 99%
“…Our study joins a limited number of studies evaluating the impact of cropland and urbanization on the genetic structure of plant populations. Prior landscape genetic studies on forbs have emphasized the role of topographic or climatic variables on population genetic structure (Lee & Mitchell-Olds, 2011;Muñoz-Pajares et al, 2017;Rhodes et al, 2014). We are aware of only a few studies be- a IBR was modelled using two methods, least cost path cost distance (LCP) and Circuitscape.…”
Section: Discussionmentioning
confidence: 99%